Augmented reality in the tourism industry: A multi-stakeholder analysis of museums - Serravalle, Francesca; Ferraris, Alberto; Vrontis, Demetris; Thrassou, Alkis; Christofi, Michael (Tourism management perspectives, 2019)
In places of tourist interest and attractions, such as museums, Augmented Reality (AR) is an emerging technology that enhances (through additional digital contents) and leverages visitor experience creating opportunities for an array of immediate and peripheral stakeholders. However, to achieve this, both researchers and managers need to better understand how to effectively co-create value through the involvement of different stakeholders and their interconnected relationships. Thus, we analysed three interrelated streams of literature (digital innovation, tourism management and stakeholder theory) and we developed a conceptual paper that sheds light on AR in museums. An in-depth analysis of the topic allowed us to develop theoretical propositions and applications on the subject, in particular from a multi-stakeholder perspective. Finally, our research proposes a preliminary conceptual model that highlights the need for the identification of the roles and interactions of museum's stakeholders towards a more digitalised museum experience through AR. •Technological advancements are expanding the innovative potential and creative opportunities of businesses.•Augmented reality is increasing engagement in visitors’ experience in museum.•Stakeholders around a museum could increase value co-creation of contents.•Using AR in museum could create engagement, and so the sharing of information and personal data with the organization.